1979
DOI: 10.1017/s0016756800044459
|View full text |Cite
|
Sign up to set email alerts
|

Early Tertiary bentonites from Svalbard

Abstract: Paleontol'ogical and petrological studies of clay beds in the Basilika Formation (Tertiary age) are presented. The petrology of the beds indicates that their main constituents were derived from volcanic activity and represent bentonites. Differing composition between beds suggests several spatially separated eruptions. The volcanic source area probably lay towards the N of the present Tertiary outcrops of Svalbard. Two foraminiferal assemblages are found in the bentonites: the lower is dominated by arenaceous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…They were first described by Gripp (1927) as thin, laterally consistent beds of plastic clay and have been observed in several locations within the CTB (Nagy, 1966;Vonderbank, 1970;Major and Nagy, 1972;Dypvik and Nagy, 1978;Major et al, 2001). Dypvik and Nagy (1978) described the bentonites as very fine-grained but poorly sorted, with maximum grain sizes between 15 and 40 µm and consisting of ∼80% clay minerals-mostly illite/smectitewith minor fractions of quartz and feldspar, indicative of altered, aeolian-transported volcanic material. Based on the grain size they concluded that the source area was located at a distance of 100−200 km from the area of deposition but more distant sources were not excluded.…”
Section: Stratigraphy Of the Central Tertiary Basin (Ctb)mentioning
confidence: 92%
See 4 more Smart Citations
“…They were first described by Gripp (1927) as thin, laterally consistent beds of plastic clay and have been observed in several locations within the CTB (Nagy, 1966;Vonderbank, 1970;Major and Nagy, 1972;Dypvik and Nagy, 1978;Major et al, 2001). Dypvik and Nagy (1978) described the bentonites as very fine-grained but poorly sorted, with maximum grain sizes between 15 and 40 µm and consisting of ∼80% clay minerals-mostly illite/smectitewith minor fractions of quartz and feldspar, indicative of altered, aeolian-transported volcanic material. Based on the grain size they concluded that the source area was located at a distance of 100−200 km from the area of deposition but more distant sources were not excluded.…”
Section: Stratigraphy Of the Central Tertiary Basin (Ctb)mentioning
confidence: 92%
“…The NALIP is expressed in flood basalts on eastern Greenlandas well as flood basalts and alkaline tuffs in western central Greenland (Storey et al, , 2007Tegner et al, 1998;Larsen and Pedersen, 2009;Larsen et al, 2016). Moreover, Paleocene bentonites were observed on Svalbard as well as Ellesmere Island and are particularly widespread in the North Atlantic region (Figure 1; Major and Nagy, 1972;Dypvik and Nagy, 1978;Larsen et al, 2003a;Grist and Zentilli, 2004;Reinhardt et al, 2013).…”
Section: Cretaceous-paleogene Geology Of Svalbard and Regional Tectonmentioning
confidence: 99%
See 3 more Smart Citations